2009
DOI: 10.1021/ja809550u
|View full text |Cite
|
Sign up to set email alerts
|

The Nature of Radiative Transitions in O-Doped Boron Nitride Nanotubes

Abstract: Recent measurements on cathodoluminescences spectra of natural and isotope-substituted boron nitride nanotubes (BNNTs) surprisingly suggest the existence of pronounced radiative transitions in BN tubes, which are possibly induced by the oxygen substitutional impurities of the samples. [Han, W. Q. et al. Nano Lett. 2008, 8, 491] However, the structural pattern of the O-doped BN tube is unknown, as a result, how does the substitutional impurity in BNNT contribute to the observed radiative transitions is still a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 47 publications
(58 reference statements)
3
32
0
Order By: Relevance
“…This is in agreement with the results obtained by Arenal et al [22]. In addition, Gou et al [23] also found that the local structure of B 3 O 6 group is emerged by the extra geometrical constraint, which may be considered as a proceeding species during the BN synthesis process. To the best of our knowledge, there is no investigation on this issue of the oxidation of graphitic BN sheet though new theoretical [23] and experimental [24] investigations emerge.…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is in agreement with the results obtained by Arenal et al [22]. In addition, Gou et al [23] also found that the local structure of B 3 O 6 group is emerged by the extra geometrical constraint, which may be considered as a proceeding species during the BN synthesis process. To the best of our knowledge, there is no investigation on this issue of the oxidation of graphitic BN sheet though new theoretical [23] and experimental [24] investigations emerge.…”
Section: Introductionsupporting
confidence: 91%
“…It is just a segment of the boroxol groups B 3 O 6 described in Ref. [23], which is a common boron oxide used frequently in the synthesis of BN nanotubes [22]. The uncompleted B 3 O 6 structure, i.e., B 3 O, behaves very unstable with strong oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For reason, BNNTs with the small diameter were suggested as an aspirant for a synthetic aquaporin-1 water channel [57]. A variety of subjects of BNNTs have been investigated by theoretical methods, including hydrogen storage [60,61,62,63,64,65,66], magnetism [67,68,69,70,71,72,73], phonon characteristics [74,75,76], stability [77,78,79], molecular dynamics [80,81,82,83], field-electron emission [84], scanning tunneling microscopy simulation [85], electron transport [86], symmetry breaking [87], work function [88], spin-splitting [89] and quantum computing [90,91]. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the calculated values of the electronic band gabs for the nanotubes might be reasonable. Various methods have been developed to tune the electronic structure of BNNTs is nicely discussed by Chunyi Zhi et al [57], for instance, applying electric field [133,134,135,136,137,138] or strain [139], or chemical methods, like doping [140,141,142,67], introducing defects [143,144,145] or surface modification [60,146,147]. The methods and species chosen are summarized in Table 2 in Ref.…”
mentioning
confidence: 99%